2009
DOI: 10.1155/2009/249840
|View full text |Cite
|
Sign up to set email alerts
|

Role for Endovascular Therapy in Chronic Mesenteric Ischemia

Abstract: Chronic mesenteric ischemia is a rare condition that is caused by stenosis or occlusion of the mesenteric arteries and usually manifests as abdominal pain. While surgical revascularization has been the standard treatment for symptomatic patients, recent advances in interventional devices and techniques have made endovascular treatment feasible and effective. Percutaneous transluminal angioplasty with stent placement is now recognized as a minimally invasive means of obtaining good long-term results with an acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
0
31
0
1
Order By: Relevance
“…Multisliced CT is a noninvasive technique, which can play a pivotal role in diagnosing vascular disease of the celiac trunk and SMA in chronic ischemia. In addition, MRI and MRA are very promising diagnostic modalities when combined with fast contrastenhanced (CE) techniques [5,35] . While AMI is an emergency where CT scanning is the most appropriate diagnostic tool, CMI is best examined with CEMRA, coupled with measurements of flow.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisliced CT is a noninvasive technique, which can play a pivotal role in diagnosing vascular disease of the celiac trunk and SMA in chronic ischemia. In addition, MRI and MRA are very promising diagnostic modalities when combined with fast contrastenhanced (CE) techniques [5,35] . While AMI is an emergency where CT scanning is the most appropriate diagnostic tool, CMI is best examined with CEMRA, coupled with measurements of flow.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…ER appears to have lower postoperative mortality and morbidity rates and shorter intensive care unit and hospital stay. Therefore, ER has been proposed for high risk surgical candidates or those with short life expectancy due to its minimally invasive nature [35,52,53] . In ER, a short stump of the patent artery is necessary to gain wire access.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Despite its prevalence, the majority of these patients are asymptomatic as a result of the extensive collateral circulation between the celiac trunk, superior mesenteric artery (SMA) and inferior mesenteric artery (IMA). Whether or not ischaemia ensues depends on the site of the stenosis or occlusion and the development or otherwise of collateral vessels (Loffroy et al, 2009). CMI typically occurs in patients who have SMA lesions in conjunction with lesions in either the celiac trunk or IMA.…”
Section: Chronic Mesenteric Ischaemiamentioning
confidence: 99%
“…Balloon-expandable stents are preferred because of their accuracy and ability to generate considerable radial force. More distal or long lesions may be better suited to self-expandable stents given their flexibility (Loffroy et al, 2009). Kougias et al (2007) reported that technical success was significantly higher with stenting compared with angioplasty alone (95% vs 83%, p=0.007), although the rate of restenosis was also higher in the stented subgroup, a finding that may have been biased by the inclusion of earlier studies where more primitive stents were used and peri-procedural anticoagulant and antiplatelet treatment regimens were not standardized.…”
Section: Angioplasty Vs Stentingmentioning
confidence: 99%
See 1 more Smart Citation